Portable low-cost water purification system for populations in developing countries and emergency use - Kee, Kelvin Ming Ern (2023)
Access to clean water is a major challenge, especially for developing countries facing water-related emergencies. Therefore, this study aims to propose a lowcost, portable water purification system that utilises agricultural waste as filter media. The filter media used were corn cobs, modified activated carbon (AC) and fruit peels (orange, dragon fruit, and banana peels) housed in a plastic drawer. This study evaluated the performance of the fruit peels in removing Fe3+ ions at different pH levels and concentrations. Additionally, this study also tested the antibacterial properties of AC coated with silver nanoparticles. Results showed that the best Fe3+ biosorption occurred when the initial concentration of Fe3+ was 25 mg/L at pH 7. The values of the maximum percentage removal of Fe3+ were 94.2879 %, 94.2358 % and 92.4361 % for banana, orange and dragon fruit peels, respectively. Furthermore, the ANOVA analysis results suggested that the type of fruit peels was insignificant as the biosorption capabilities of the proposed fruit peels were comparable under optimum conditions. Hence, orange, dragon fruit and banana peels are good candidates for Fe3+ removal. Besides, the AC coated with silver nanoparticles did inhibit the growth of E.coli, making it an excellent material for contaminant removal and water disinfection. Moreover, the proposed filtration system was able to reduce the Fe3+ concentration, conductivity, and turbidity values of the synthetic polluted water by 98.62 %, 40.00 %, and 81.73 %, respectively, indicating that agricultural wastes could potentially treat wastewater. However, further improvements are required to obtain safe water for human consumption as the treated water had yet to achieve potable standards, and its COD value increased by 247.06 %. The methods for improvement include optimising filter media depth and proper pre-treatments of biosorbents. It is also recommended to study the biosorption mechanism, kinetics, and reusability of the biosorbents to develop an economically feasible and environmentally sustainable water purification system.